The nature, use and validity of subordination agreements to auditors of South African companies - Bosman, Michael John (Department of Commercial Law, 2023)
Subordination or 'backranking' agreements have been used by auditors in South Africa in companies where liabilities exceed assets, fairly valued. In the light of recent judgements handed down by Stegmann J, especially in the case of Ex parte De Villiers and Another NNO: In re Carbon Developments (Pty) Ltd 1992 (2) SA 95 (W) the nature, use and validity of subordination agreements has been questioned. In the view of Stegmann J, a situation in a company where its liabilities exceed its assets, fairly valued or a situation where it is unable to pay its debts, renders that company insolvent. As a result it is liable to be wound up if it is not recapitalized as a matter of urgency. From an auditor' s point of view this renders the 'going concern' concept to be inappropriate to the company which must result in a qualified audit report being issued by the auditor. In addition, in the view of Stegmann J, a material irregularity as contemplated in terms of section (20) (5) of the Public Accountants' and Auditors' Act, 80 of 1991 has arisen, and must be reported the Public Accountants' and Auditors' Board. This view is contrary to present thinking in the accounting profession. In this paper the role of an auditor in a company with respect to the nature of material irregularities is examined especially with regard to those companies which are prima facie or "technically" insolvent in that their liabilities exceed their assets. The concepts of 'going concern', ' insolvency' , 'trading when the liabilities of a company exceed its assets', and the 'inability of a company to pay its debts' are studied. The criticisms levied at and practical problems associated with subordination agreements are examined and discussed. It is submitted that subordination agreements do have value and use for auditors. However, the status quo needs clarification to avoid confusing standards from existing between companies, public accountants and auditors, and insolvency practitioners.